Biodistribution Study of Niosomes in Tumor-Implanted BALB/C Mice Using Scintigraphic Imaging - Leanne De Silva; Ju-Yen Fu; Thet Thet Htar; Wan Hamirul Bahrin Wan Kamal; Azahari Kasbollah; Saravanan Muniyandy; Lay-Hong Chuah (Frontiers Media S.A., 2022)
The purpose of this work was to study the biodistribution of niosomes in tumor-implanted BALB/c mice using gamma scintigraphy. Niosomes were first formulated and characterized, then radiolabeled with Technetium-99 m (99mTc). The biodistribution of 99mTc-labeled niosomes was evaluated in tumor-bearing mice through intravenous injection and imaged with gamma scintigraphy. The labeled complexes possessed high radiolabeling efficiency (98.08%) and were stable in vitro (>80% after 8 h). Scintigraphic imaging showed negligible accumulation in the stomach and thyroid, indicating minimal leaching of the radiolabel in vivo. Radioactivity was found mainly in the liver, spleen and kidneys. Tumor-to-muscle ratio indicated a higher specificity of the formulation for the tumor area. Overall, the formulated niosomes are stable both in vitro and in vivo, and show preferential tumor accumulation.